Electrochemical evaluation of extremely-low frequency magnetic field effects on sulphate-reducing bacteria - Fojt, Lukáš; Vetterl, Vladimír (Folia biologica (Praha), 2012)
The effects of 50 Hz magnetic fields on sulphate- reducing bacteria viability were studied electrochemically. Two types of graphite electrodes (pyrolytic and glassy carbon) covered with whole bacterial cells behind a dialysis membrane were used for electrochemical measurements. We found about 15% decrease of reduction peak current density (which indicates desulphurization activity of the bacterial cells - their metabolic activity) on cyclic voltammograms after magnetic field exposure compared to the control samples. We suppose that the magnetic field does not influence the metabolic activity (desulphurization) of sulphate-reducing bacteria but most probably causes bacterial death.
Keywords: elektrochemické techniky; Electrochemical Techniques; Magnetic Fields; Sulfates; Desulfovibrio; elektrody; sírany; Electrodes; Desulfotomaculum; Carbon; uhlík; mikrobiální viabilita; Microbial Viability; magnetické pole